Pengaruh Lifestyle, Customer trust, dan Product review terhadap Purchase decision (konsumen Alicia Skincare Clinic Purwodadi) - Dea Puspita Rini; Sri Martono (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2025)
The skincare industry in Indonesia is rapidly growing, creating the need to understand consumer behavior in local markets such as Purwodadi. Alicia Skincare Clinic attracts consumers with affordable and tailored products, while purchase decisions are shaped by lifestyle, customer trust, and product reviews. Since previous studies show inconsistent results regarding these factors, this study aims to examine their influence on purchase decisions at Alicia Skincare Clinic Purwodadi to provide useful insights for improving marketing strategies.  This study adopts a quantitative approach with a survey method. Questionnaires were distributed to 70 active consumers of Alicia Skincare Clinic Purwodadi, chosen through a simple random sampling technique. The data obtained were analyzed using multiple linear regression with SPSS version 26 to evaluate the effects of lifestyle, customer trust, and product reviews on purchase decisions.  The findings indicate that lifestyle, customer trust, and product reviews positively and significantly affect purchase decisions, both partially and collectively. Of these variables, lifestyle emerges as the most dominant factor influencing consumer decisions at Alicia Skincare Clinic Purwodadi.   The study concludes that lifestyle, customer trust, and product reviews significantly influence purchase decisions, with lifestyle being the most dominant factor. Businesses, especially Alicia Skincare Clinic, should focus on aligning their products with consumers’ lifestyles, strengthening trust through quality and safety, and encouraging positive reviews to enhance competitiveness. Future research is suggested to explore additional factors influencing consumer behavior for broader insights.